2015
DOI: 10.1002/chem.201501675
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Binding Inhibits Nuclear Uptake of Luminescent Metal‐Complex‐Based DNA Imaging Probes

Abstract: The DNA binding and cellular localization properties of a new luminescent heterobimetallic Ir(III) Ru(II) tetrapyridophenazine complex are reported. Surprisingly, in standard cell media, in which its tetracationic, isostructural Ru(II) Ru(II) analogue is localized in the nucleus, the new tricationic complex is poorly taken up by live cells and demonstrates no nuclear staining. Consequent cell-free studies reveal that the Ir(III) Ru(II) complex binds bovine serum albumin, BSA, in Sudlow's Site I with a similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…86,89 Interestingly, a subsequent study by the authors revealed that incorporation of two benzo[h]quinolone cyclometalating ligands around the Ir centre resulted in the complex 17 displaying an even higher rate of nuclear accumulation, relative to complex 16. 90 However, when cells were incubated with complex 17 in serum-containing medium, both the uptake and localisation of the complex dramatically changed, as shown in Fig. 5c.…”
Section: Cellular Uptake and Localisationmentioning
confidence: 94%
See 2 more Smart Citations
“…86,89 Interestingly, a subsequent study by the authors revealed that incorporation of two benzo[h]quinolone cyclometalating ligands around the Ir centre resulted in the complex 17 displaying an even higher rate of nuclear accumulation, relative to complex 16. 90 However, when cells were incubated with complex 17 in serum-containing medium, both the uptake and localisation of the complex dramatically changed, as shown in Fig. 5c.…”
Section: Cellular Uptake and Localisationmentioning
confidence: 94%
“…With regards to cellular uptake and localisation, the lipophilicity of complexes has been further shown to play a profound role in both processes. 47,63,86,89,90,104 For example, the formation of lipophilic ion-pairs has recently been demonstrated to promote the cellular uptake and nuclear localisation of complexes which had previously been unable to enter live cells; 107 a strategy which could prove beneficial for other systems in the future. However, while increasing the lipophilicities of complexes can improve their uptake, it can also have a considerable impact on the nature of their interactions with biomolecules, such as proteins and membranes, which may in fact hinder their uptake, alter their subcellular localisation and/or influence the nature of their interactions with (or even the identity of) their molecular targets within cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a program to identify oligonuclear complexes that recognize biologically relevant ions and biomolecules, the Thomas group has been investigating the biological properties of Ru II , Os II , and Ir III complexes containing the rigidly planar poly-aromatic ligand tetrapyridophenazine, tpphz. [45][46][47][48][49][50] Most of this work has centred on their bio-imaging and therapeutic potential with eukaryotic cells. Butas our original report on cell imaging showed that the prototype system, [{Ru(phen) 2 } 2 (tpphz)] 4+ , 1 4+ , was readily taken up by S. aureus cells 46we set out to develop new dual imaging/antimicrobial theranostics based on this architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, this allows for the harvesting of both singlet and triplet excitons within an OLED, theoretically allowing 100% internal quantum, and since their first deployment in these devices by Forrest et al, they have been the subject of numerous patents and papers. [12][13][14][15][16][17][18][19][20][21] Their emission spectra can be readily tuned by altering either the ancillary or 2-phenylpyridine ( ppy) ligand. [12][13][14][15][16][17][18][19][20][21] Their emission spectra can be readily tuned by altering either the ancillary or 2-phenylpyridine ( ppy) ligand.…”
Section: Introductionmentioning
confidence: 99%